(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Premessa - 2. Considerazioni preliminari - 3. La fine del ‘vecchio mondo’ - 4. Universalità e identità - 5. Un nuovo protagonismo per i diritti religiosi? - 6. Per concludere. Secularism and post-modernity: some American echos ABSTRACT: The paper focuses on the works of six North American authors stemming from the conviction that the end of the ‘modern world’ is nigh and we are locked into the irreversible entropy of a secularism understood as a wall of separation between politics and religion. These convictions, together with a strong criticism towards legal positivism, imply the idea of the porousness of the borders between the sacred and profane, and a resulting reciprocal adjustment, an osmosis between the political and the religious spheres. In this paper, I would like to concentrate on the new approaches proposed by these authors and on the historical end epistemological connotations of the posited osmosis between the political and religious spheres.